MEKANISME PENYELESAIAN SENGKETA HUBUNGAN INDUSTRIAL SECARA WIN-WIN SOLUTION - Mashari S.H., M.H. (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2010)
Industrial relations dispute settlement can be done through litigation and nonlitigation. The process of settlement of disputes through litigation in the courts, resulting in agreements that are not yet able to embrace the adversarial common interests, tend to cause new problems, slow in its solution, requiring expensive, unresponsive, and caused animosity between the parties. While the dispute settlement process through non-litigation out of court to produce an agreement that is win-win solution, which guaranteed the confidentiality of the dispute by the parties, to avoid delays caused due to procedural and administrative problems in a comprehensive settlement in togetherness, and still maintain good relations . The only advantage of non-litigation process is the nature of confidentiality, because the process of trial and even the decision was not made public. Dispute settlement mechanism is a win-win solution can be done in stages: first stage Bipartite tail, a settlement through consultation between workers with employers without the intervention of third parties. The second stage through mediation, which is implemented by the Government settlement through a mediator which is responsible for mediation can be a mediator in resolving disputes between workers with employers, or through conciliation, the conciliation officer is appointed and dismissed by the Secretary of Labor based on advice union organization or unions. However, if the settlement is not reached agreement may be pursued to the Indonesian National Arbitration Board conducted by the National Arbitrator, and succeeded in reaching an agreement made when the deed of settlement which is binding (the final and binding).